Implementasi Pembelajaran Seni Musik terhadap Perkembangan Kognitif Anak di TK Karya Bunda Mandiri Medan - Zahra, Sofia; Nabila, Sarah; Andini, Zyhan Risty; Lubis, Hilda Zahra (AS-SABIQUN, 2024)
Learning the art of music on cognitive development in early childhood is discussed in this research. Learning the art of music in early childhood is the main thing and is very important to learn and develop in early childhood. This research aims to find out how teachers implement music arts learning for early childhood at Karya Bunda Mandiri Kindergarten in Medan. early childhood education programs. The method used in this research is a qualitative approach. Then the data collection techniques used were observation and literature study. The data analysis technique used is descriptive analysis. The results of the research show that learning the art of music is very important and has an influence on children in their development process and from the results of research at the Karya Bunda Mandiri Kindergarten in Medan, teachers have implemented early childhood education music learning well and in fun and can improve children's cognitive abilities because in teacher learning always uses singing and clapping to teach new things in learning at Karya Bunda Mandiri Kindergarten.